PENGARUH DUKUNGAN MANAJEMEN DAN KAPABILITAS AUDITOR INTERN TERHADAP PENCEGAHAN DAN PENDETEKSIAN FRAUD - Sofie Noor Sofiyani (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2018)
The purpose of this study was to describe (1) Management Support, Intern Auditor’s Capability, Prevention and Detection Fraud; (2) Influence of Management Support and Intern Auditor’s Capability on Prevention and Detection Fraud in partially; (3) Influence of Management Support and Intern Auditor’s Capability on Prevention and Detection Fraud in simultaneously. This research used descriptive method with survey approach. Data collection implemented by primary data that obtained directly from subject at Inspektorat of Tasikmalaya City and secondary data from literature. Result showed: (1) Management Support, Intern Auditor’s Capability, Prevention and Detection Fraud was very good; (2) Partially, Management Support and Intern Auditor’s Capability has a significantly effect on Prevention and Detection Fraud; (3) Simultaneously, Management Support and Intern Auditor’s Capability has a significantly effect on Prevention and Detection Fraud